How Rwanda mounted a research response with an investigational vaccine just ten days into a Marburg outbreak - Sabin Nsanzimana; Noella Bigirimana; Richard Hatchett; Sue Bailey; Natacha Butera; Yvan Butera; Jakob P. Cramer; Amy Finan; Caroline M. Forkin; Adam M. Hacker; Sibomana Hassan; Vicky Leamy; et al. (npj Vaccines)
Abstract The September 2024 outbreak of Marburg virus disease (MVD) represented the first time this virus was identified in Rwanda. Health authorities mounted a rapid and effective response, including the rapid execution of an open-label Phase 2 clinical trial of an investigational Marburg vaccine, beginning just 10 days after the outbreak was declared. We share lessons from this rapidly executed clinical trial to help encourage outbreak research preparedness in other countries.